2006
DOI: 10.1111/j.1365-3113.2006.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Speciation in Pararge (Satyrinae: Nymphalidae) butterflies – North Africa is the source of ancestral populations of all Pararge species

Abstract: Abstract. The genus Pararge comprises three species: P. aegeria, distributed in Europe and North Africa; P. xiphia, endemic to Madeira; and P. xiphioides, endemic to the Canary Islands. Two subspecies are recognized in P. aegeria, P. a. tircis and P. a. aegeria, distributed in northern and southern Europe, respectively. In the 1970s, P. aegeria appeared on Madeira. However, despite the status of P. aegeria as a model species in ecological studies, the evolutionary history of Pararge remains unknown. We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 64 publications
5
36
0
Order By: Relevance
“…all Maghreb species of Calomera , Cephalota , Cylindera , and Grammognatha ) (Putchkov and Matalin 2003; Serrano 2013). Similar patterns in faunal elements have been noted also among other groups of invertebrates, including some groups of insects (Weingartner et al 2006; Riservato et al 2009; Habel et al 2008), scorpions (Gantenbein and Largiadèr 2003), amphibians and reptiles (Busack 1986; Schleich et al 1996; Alvarez et al 2000; Cox et al 2006), mammals (Dobson 1998; Cosson et al 2005; Temple and Cuttelod 2008; Skog et al 2009) and plants (Thompson 2005). …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…all Maghreb species of Calomera , Cephalota , Cylindera , and Grammognatha ) (Putchkov and Matalin 2003; Serrano 2013). Similar patterns in faunal elements have been noted also among other groups of invertebrates, including some groups of insects (Weingartner et al 2006; Riservato et al 2009; Habel et al 2008), scorpions (Gantenbein and Largiadèr 2003), amphibians and reptiles (Busack 1986; Schleich et al 1996; Alvarez et al 2000; Cox et al 2006), mammals (Dobson 1998; Cosson et al 2005; Temple and Cuttelod 2008; Skog et al 2009) and plants (Thompson 2005). …”
Section: Discussionsupporting
confidence: 56%
“…First is the topographic position of Maghreb within the West Palaearctic realm as the area was (and still is, mainly because of Gibraltar and Sicily sea straits) an important natural bridge between European and African faunas (eg. Harris et al 2002; Paulo et al 2002; Carranza et al 2004, 2006; Veith et al 2004; Fritz et al 2006; Weingartner et al 2006; Recuero et al 2007; Habel et al 2008, 2010; Skog et al 2009). As a result of these biogeographical links between both continents at different times, presently Maghreb region is inhabited by a mixed tiger beetle fauna with representatives of 22 species belonging to eight different groups according to their chorotypes (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The prediction model assumes that the ancestral population over the whole continental studied area was the western one. This is suggested by the unexpected presence of the western lineage in several Italian islands and by the recent findings of Weingartner, Wahlberg & Nylin (2006), who revealed that the North African population of the Satyrinae butterfly Pararge aegeria (Linnaeus) represents the ancestral lineage for all European species and forms of Pararge. Thus, the centroid value of Cv of the African source is assumed to be the ancestral form (Cv A).…”
Section: Refugial Hypothesismentioning
confidence: 88%
“…These findings also expand our knowledge on European post glacial colonization history from Mediterranean refuges. To date, five of the potential combinations of colonization pathway, referred to as colonization paradigms (Hewitt, 1999(Hewitt, , 2000Schmitt, Gießl & Seitz, 2003;Schmitt, Röber & Seitz, 2005;Habel, Schmitt & Müller, 2005;Habel et al, 2008;Weingartner et al, 2006;Schmitt, 2007), have been described emanating from four mainland areas: Iberia, Italy, the Balkans, and North Africa. These pathways focus attention on movement north into Europe from the Mediterranean.…”
Section: Modelling Affiliations Between Island and Source Populationsmentioning
confidence: 98%
“…In order to decide which species to contrast with each other we used phylogenetic information from recent molecular studies when available (Brunton 1998;Wahlberg and Zimmermann 2000;Zimmermann et al 2000;Wahlberg and Nylin 2003;Kandul et al 2004;Simonsen 2005;Weingartner et al 2006;U. Kodandaramaiah & N. Wahlberg, unpublished Coenonympha phylogeny), and in other cases we had to rely on traditional classification (Higgins 1975).…”
Section: General Methodologymentioning
confidence: 99%